Accounting for concrete plastic-damage and steel bars ductile-damage when modeling reinforced concrete columns in finite element applications - Zad, Nader (Kansas State University, 2023)
Testing full-scale structures in the laboratory is neither always doable nor financially feasible, especially for large structures. Therefore, these structures are often modeled with Finite Element Analysis (FEA) software and packages, such as Abaqus, to understand their actual behaviors under special simulated loading and material-behavioral considerations. The work in this dissertation addresses two main issues: The first is the accurate modeling of the material to account for plastic damage of the concrete, and the other is the modeling of the steel used in the reinforcement including the ductile damage of the metal. The study of the concrete material is aimed at developing a material model that simulates load-induced cracking in reinforced concrete (RC) elements in the FEA structures. The simulation of complete stress-strain concrete behavior under tension and compression (including damage characteristics) requires the application of numerical material models, potentially producing the stress-strain curves. These models include strain-softening regimes that presuppose the use of ultimate compressive concrete strength and that can be practically implemented for existing or future RC structures. The method presented in this study is valuable because it assesses existing RC structures when detailed test results are not available. However, the implemented numerical models were slightly altered in order to compare them with the damage plasticity models available in the research literature. These mainly are the smeared crack concrete model, the brittle crack concrete model, and the concrete damage plasticity model, which are all typically suitable for RC elements. The methodologies proposed here provide accurate and realistic modeling of the plastic damage of reinforced concrete members. Although numerically extensive and very time-consuming, it is demonstrated that the material and damage modeling presented in this research study can be used to accurately represent the behavior of actual structural members tested in research laboratories. This suggests that it is applicable to structures for which experimental tests or monitoring data are not available. With regards to the steel reinforcement, the structural steel modeling for cyclic response is essential for the functioning appraisal and design of steel structures. Though various mathematical models have been suggested and developed to simulate metal plasticity, only a few of them have been implemented in finite element method-based software such as Abaqus, which uses incremental plasticity procedures. This part of the dissertation research introduces and briefly describes a built-in “Isotropic, Kinematic, Johnson-Cook, User and Combined” hardening to model metal plasticity under cyclic loading. The plastic deformation is load path-dependent and irreversible. Implementation of this model is fundamentally significant for Abaqus users to increase understanding of the behavior and plasticity of steel and reinforced (concrete) structures.
Keywords: Plastic-damage (damage plasticity); Concrete; Abaqus; Cracking; Behavior; Compression; Tension; Material model; Stiffening; Ductile-damage; Steel; Cyclic; Plasticity; Finite element method (FEM); Isotropic; Kinematic; Combined hardening; Stress; Strain; Uniaxial; Elastic; Plastic; Yielding; Softening